Long non‐coding RNAs as an epigenetic regulator in human cancers. Issue 10 (30th August 2017) - Kondo, Yutaka; Shinjo, Keiko; Katsushima, Keisuke
Abstract : Recent studies have described the important multiple roles of long non‐coding RNAs (lncRNAs) during oncogenic transformation. Because the coding genome accounts for a small amount of total DNA, and many mutations leading to cancer occur in the non‐coding genome, it is plausible that the dysregulation of such non‐coding transcribes might also affect tumor phenotypes. Indeed, to date, lncRNAs have been reported to affect diverse biological processes through the regulation of mRNA stability, RNA splicing, chromatin structure, and miRNA‐mediated gene regulation by acting as miRNA sponges. Furthermore, accumulating studies have described the roles of lncRNAs in tumorigenesis; however, the precise mechanisms of many lncRNAs are still under investigation. Here, we discuss recently reported mechanistic insights into how lncRNAs regulate gene expression and contribute to tumorigenesis through interactions with other regulatory molecules. We especially highlight the role of taurine upregulated gene 1, which was recently reported to have biological functions related to gene regulation, and discuss the future clinical implications of lncRNAs in cancer treatments. Abstract : Understanding how lncRNAs and epigenetic regulators communicate with each other and affect gene expression is important and challenging issue to yield better options for cancer treatments. Here, we describe recently reported mechanistic insights into how lncRNAs regulate gene expression and contribute to tumorigenesis via interactions with other regulatory molecules. We also discuss the future clinical implications of lncRNAs in cancer treatments.